THANKLESS IN DEATH - Robb, J. D., 1950-, author (Great Britain : piatkus, 2013)
As the household of NYPSD Lieutenant Eve Dallas and her billionaire husband Roarke prepares for an invasion of family and friends for Thanksgiving, an ungrateful son decides to stop the nagging from his parents - by ending their lives. Soon Jerald Reinhold is working his way through anyone who has ever thwarted him in his path to an easy life. Eve is increasingly frustrated in her efforts to cover all the potential victims as Jerald stays a terrifying step ahead. As the festivities begin, Eve is desperate to identify which victim on Jerald's long list will be the next, so she can stop the killing spree.